خصائص موجات الحر وتأثيراتها البيئية في العراق - الموسوي، علي صاحب طالب Almousawi, Ali Saheb Taleb; شبر، مهند حطاب Shubar, Muhannad Hattab (جامعة الكوفة - مركز دراسات الكوفة, 2016)
The study aims to reveal the severe thermal properties of Iraq that lies between latitudes (20 – 5 29- 50-22 37) north and the longitudes (42 38- 45 48) east and (59 31) north. This location makes most of the areas in Iraq within the thermal excessiveness in the world which lies between the tropical latitude and latitude 35 north and south. Moreover, there are many geographical factors that make Iraq one of the areas that suffers severe ecological conditions represented by the hot waves. The geographical and astronomical location have the greatest effect in that. Also, the nature of the surface and the height decide the pressure systems, their period and intensity. The study adopted daily and hourly data collection recorded in the Iraqi metrology for a number of climatic elements for the period 1941-2013 in three stations (Musol, Baghdad, Basrah) which covers almost most of the areas of Iraq. The study also focused on the consequences of these waves and the relation between them. . The study also reached that there is an effect caused by the waves on the weather properties accompanying them in the study area which will be obvious in the various environmental elements through hourly and daily comparison of the weather properties for the days of hot waves by monthly rates and in the days preceding the occurrence of the waves
جاء هذا البحث بهذا العنوان لكي يبرز دور موجات الحر في التأثير على البيئة، ونظرا لسعة الموضوع فان ذلك يتطلب وضع فرشة جغرافية تعتمد على الخصائص المناخية التي ترافق موجات الحر وهذا سيكون قاعدة عامة للدراسات اللاحقة التي تدرس علاقة موجات الحر أو موجات البرد بكل جانب محدد من جوانب البيئة. يركز هذا البحث على التأثيرات التي تقوم بها موجات الحر على عناصر المناخ الرئيسية والتي تقوم هي الاخرى بالتأثير في جوانب البيئة الاخرى، لما لعناصر المناخ من ارتباط متداخل فيما بينها من جهة، وارتباط تلك العناصر في الخصائص المناخية والبيئية الأخرى من جهة أخرى إذ يرتبط المناخ في البيئة بعلاقة وطيدة بحيث يؤثر كل عنصر في الآخر، لذا فإن أي تغير وكيفما كان بسيطا في المناخ يؤثر سوآءا بطريقة مباشرة أو غير مباشرة في البيئة، وبذلك فنحن سنختصر الطريق على الكثير من الدراسات التي تروم القيام بدراسة تأثير موجات الحر في جوانب البيئة المختلفة، فضلا عن أننا سنوفر قاعدة معلومات مهمة تستخرج من البيانات اليومية والساعية لخصائص عناصر المناخ المرافقة لأيام موجات الحر والبرد وكيف تختلف تلك الخصائص أثناء مرافقتها لأيام موجات الحر عن المعدلات الشهرية لها، فضلا عن أننا سنقوم بدراسة تلك الخصائص المناخية المرافقة لموجات الحر ساعيا واختلافها عن الأيام التي سبقتها، وبالتأكيد ستفيد كثيرا نتائج الدراسة هذه كل القطاعات البيئية المختلفة كالقطاع الصحي، والزراعي، والصناعي، وقطاع الكهرباء وغيرها ....
Keywords: الطقس -- المناخ -- الجغرافيا الطبيعية -- مناخ العراق